Perbandingan Gaya Hidup Sehat antara Siswa Laki-Laki dan Perempuan SMP di Surabaya - Alina Novia Pudya Bareta; Faridha Nurhayati (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aims to analyze the comparison of healthy lifestyles between male and female students at the junior high school level. The research uses a quantitative approach with a comparative design. Data were collected using a questionnaire, resulting in 252 respondents comprising 115 male students and 137 female students. Data analysis was conducted using the Mann-Whitney test because the data were not normally distributed. The healthy lifestyle in this study includes seven indicators as well as a total healthy lifestyle score. The results indicate that there are significant gender differences in the indicators of physical activity (0.005), stress management (0.000), sleep habits (0.040), freedom from substance abuse (0.000), and the total healthy lifestyle score (0.000). Meanwhile, no significant differences were found in the indicators of healthy eating patterns (0.892), social support (0.215), and limited screen time (0.642). Male students are more physically active, whereas female students are better in stress management, sleep habits, free from substance abuse, and total healthy lifestyle scores. These findings indicate the role of gender in several healthy lifestyle indicators and provide a basis for the development of more adaptive physical education programs and school policies.